2016
DOI: 10.1108/ijlma-04-2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

Credit risk management of Ghanaian listed banks

Abstract: Purpose – The study aims to assess credit risk management practices within financial institutions in Ghana. Specifically, the study compares credit risk management practices of listed banks in Ghana with Basel II (1999). Design/methodology/approach – The analysis is based on data gathered from varied sources, namely, use of questionnaires, analysis of internal credit policies and procedure manuals and semi-structured interviews and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…In addition, whenever the CAR of the banks falls below the regulatory threshold of 10% as stipulated by the Bank of Ghana, the universal banks are left with less funds to lend to customers to attract the necessary interest income which will boost their financial performance. Comparing the results to empirical literature, this study is not consistent with the findings of Boahene et al (2012), Kolapo et al (2012), andApanga et al (2016) whose outcome found a positive relationship between financial performance and credit risk. This is because each of these studies used one proxy for credit risk and another proxy for profitability and also did not perform a path analysis with the bank specific variable which were used in the current study.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, whenever the CAR of the banks falls below the regulatory threshold of 10% as stipulated by the Bank of Ghana, the universal banks are left with less funds to lend to customers to attract the necessary interest income which will boost their financial performance. Comparing the results to empirical literature, this study is not consistent with the findings of Boahene et al (2012), Kolapo et al (2012), andApanga et al (2016) whose outcome found a positive relationship between financial performance and credit risk. This is because each of these studies used one proxy for credit risk and another proxy for profitability and also did not perform a path analysis with the bank specific variable which were used in the current study.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
“…This sample period even though improves on Amidu and Hinson (2006), is related to the situation before the credit crunch in 2008 and the euro-zone crisis which subsequently had it's real effect on the Ghanaian economy from 2012 to date. The study by Apanga et al (2016) was done post the global financial crises but the thrust of the study was the identification of the credit risk management practices and juxtaposing them with the recommendations in the Basel II accord. Nevertheless, these findings were not analysed in the context of the lemon theory through the SEM.…”
Section: Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that bank stability is an essential factor in explaining financial development (Apanga, Appiah, & Arthur, 2016;Maredza, 2015;Sarkar & Sensarma, 2016). It is plausible to argue that, when banks are stable, they will contribute positively to the development of the financial sector (Beck, De Jonghe, & Schepens, 2013;Carvallo & Pagliacci, 2016).…”
Section: Bank Stabilitymentioning
confidence: 99%
“…According to Apanga et al (2016), "credit risk practices within listed banks in Ghana are in line with sound practices. The only dissimilarity, however, is the role of the board of directors in defining acceptable types of loans and maximum maturities for the various types of loans.…”
Section: Ghana"s Financial System and Credit Riskmentioning
confidence: 99%